2022
DOI: 10.1002/agt2.277
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared fluorophores with absolute aggregation‐caused quenching and negligible fluorescence re‐illumination for in vivo bioimaging of nanocarriers

Abstract: Environment-responsive fluorophores with aggregation-caused quenching (ACQ) properties have been applied to track nanocarriers with reduced artefacts caused by unbound or free fluorophores but suffer from incomplete fluorescence quenching and significant re-illumination, which undermine bioimaging accuracy. Herein, through structural modifications to reinforce the hydrophobicity, planarity and rigidity of fluorophores with an aza-BODIPY framework, probes featuring absolute ACQ (aACQ) and negligible re-illumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…A detailed step-bystep description and discussion of in vivo live imaging has been published. 49 Conclusions ACQ fluorescent dyes have an "ON → OFF" signal conversion mode, which has broad application prospects in the field of NDDSs. Our previous studies have demonstrated the application value of ACQ dye P2; however, multiple components in the biological environment may cause the re-illumination of the quenched fluorescent aggregates.…”
Section: In Vivo Live Imaging and Evaluation Of Re-illuminationmentioning
confidence: 99%
“…A detailed step-bystep description and discussion of in vivo live imaging has been published. 49 Conclusions ACQ fluorescent dyes have an "ON → OFF" signal conversion mode, which has broad application prospects in the field of NDDSs. Our previous studies have demonstrated the application value of ACQ dye P2; however, multiple components in the biological environment may cause the re-illumination of the quenched fluorescent aggregates.…”
Section: In Vivo Live Imaging and Evaluation Of Re-illuminationmentioning
confidence: 99%
“…Pharmaceutics is an interdisciplinary field in which many subjects play important roles. [1][2][3][4][5] Particularly in this nano era, nanotechniques and the corresponding complex nanostructures they produce continuously exhibit the capability to generate novel nano-drug delivery systems (DDSs). [6][7][8][9] The three directions of nanoscience, i.e., "small size, order, and structure", aim to produce all kinds of nanomaterials with increasingly smaller sizes to create arrays of nanoproducts for functional applications and to generate new complicated nanostructures and nanodevices for tailoring functional performances.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, we consider aggregation, a spontaneous phenomenon of hydrophobic molecules in aqueous systems, will be an effective solution to increase tetrazine-chromophore proximity and interactions, enhancing tetrazine quenching effects. [23,53] However, most conventional planar fluorophores suffer from aggregation-caused quenching (ACQ) effect, [54][55][56] which diminishes post-click turn-on emission in aggregates, making it difficult to apply this aggregation strategy for fluorogenic probe designs. Therefore, we focused on aggregation-induced emission luminogens (AIEgens), a series of dyes that exhibit weak emission in dilute solutions but significantly enhanced emission in the aggregate state, to achieve this strategy.…”
Section: Introductionmentioning
confidence: 99%